Facilitating flexitarian approaches with plant-based meat analogs in line with the UN Sustainable Development Goals (SDGs) - Bogueva, Diana; Marinova, Dora (Academic Press, 2024)
Environmental change and the projections for a growing population have shifted the way people think about food. Responsible for the rapid deterioration of ecological and human well-being, the Western diet requires a dramatic change to avoid both malnourishment and undernourishment. In recent years, flexitarian ways of eating represent efforts to cut meat intake and the unsustainable high-calorie diets in high-income countries while improving human health and responding to animal welfare. Plant-based meat analogs are emerging as transition foods toward more plant-rich diets for flexitarians, meat-avoiders, and the mainstream consumer. They also contribute to the ambitious global agenda of the United Nations through the Sustainable Development Goals (SDGs). Facilitating flexitarian approaches with plant-based meat analogs aligns with many SDGs, and the chapter explores these synergies while acknowledging the need for further research and improvement to respond to any societal concerns.